Числа: [роман] / Виктор Пелевин - Пелевин Виктор Олегович (Эксмо, 2007)
Экземпляры: ф.1 (ретро) / Инвентарный номер: 42253 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 24 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-444